Problem solving from an epistemological approach (Foro de Educacion, 2020)
The relation of the subject with knowledge is an essential issue within the framework of the accelerated development of science and technology, reason that has established the learning to learn as one of the pillars of education. The forms of knowledge acquisition are diverse, but one of the most daily and innate is the resolution of problems. Such a complex context, in which an enormous amount of information is generated in an accelerated manner, suggests the need to understand and value the role of problem solving as an epistemological act, which favors the incorporation of new knowledge into the knowledge system of the subject. But, by what procedures is conducive from teaching solving problems so that the student reaches new knowledge? Various sources of information pertinent to the topic are consulted, along with several of the most outstanding trends or perspectives in the treatment of problem solving as a learning situation and its regularities. With this work a synthetic vision of the existent resources for the treatment of the resolution of problems from an epistemological approach is exposed, what propitiates a better advantage of this situation of learning oriented to learn to learn.